Inventor collaboration over distance - a comparison of academic and corporate patents - Anja Dettmann; Sidonia von Proff (Philipps-University Marburg, Department of Geography, 2010)
The paper compares academic and corporate patents in Germany to shed light on the geographical distribution of the inventors. The residences of the inventors show different patterns in the two datasets. Furthermore, we analyze the spatial distance between inventors for patents invented in collaboration and give insights into the distance's change over a time period of 14 years. The distance between collaborating inventors of corporate patents exceeds that of inventors of academic patents. In spite of the rise of ICT and cheap passenger transportation the collaboration distances have not increased. This supports earlier literature on the importance of proximity in innovation.
Keywords: R12; O34; L14; 330; inventor networks; Germany; academic patents; research collaboration